What Do We Mean by Smart Contracts? Open Challenges in Smart Contracts - Vigliotti, Maria G. (Frontiers in Blockchain, 2021)
Contracts regulate most of our professional and personal life: they enable modern society to operate. The term "Smart Contract", coined in 1994 by Nick Szabo, means different things to to different people. This editorial perspective explores the meanings of the term "smart contract" and the challenges about the legality of "smart contracts". We are familiar with contracts written in natural language, yet our relationships with smart contracts is yet to be defined. The advent of blockchain technology seems to have accelerated the development and the opportunities for the adoption of smart contracts. The purpose of this editorial is to create an interdisciplinary section where computer scientists and members of the legal profession participate in a constructive debate around smart contracts to positively influence future development.